Using Analytical Hierarchy Process (AHP) to Evaluate Barriers in Adopting Formal IT Governance Practices - Othman, Mohd Fairuz Iskandar; Che Pee, Naim; Abdul Rahim, Yahaya; Sulaiman, Hamzah Asyrani; Othman, Mohd Azlishah; Abd. Aziz, Mohamad Zoinol Abidin (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The adoption of formal standards and frameworks that facilitate effective IT Governance (ITG) continues to be an important issues by todays’ CIO’s. Organisations continue to focus their attention on adopting these formal ITG practices. However, the adoption of formal ITG practice can be a major challenge due to the existence of several barriers. Therefore, this work aims to identify and evaluate barriers related to the adoption of formal ITG practice. A total of 10 barriers in adopting formal ITG practice are listed through literature and expert inputs. The listed barriers are then evaluated to determine their relative importance using an Analytical Hierarchy Process (AHP) technique. The usefulness of the proposed work is shown by taking the case example of a financial sector organisation in Malaysia. According to the findings, the category of barriers related to “Organisational factors” was attributed the highest importance among other barriers in adopting formal ITG practices. Overall, the purpose of this work is to aid managers and practitioners through important insights as well as support their decision-making in terms of managing formal ITG practice implementation issues in the financial sector, in an effective and efficient manner.